Impact of damage on the propagation of Rayleigh waves in lattice materials. (May 2021) - Reda, H; Rahali, Y; Vieille, B; Lakiss, H; Ganghoffer, JF
We analyze in this contribution the phase velocities of Rayleigh waves in periodic beam-lattices materials. The effective mechanical properties for the virgin and damaged structures are evaluated. The damaged lattice is modeled by removing beams within full networks made of repetitive unit cells. An evaluation of the phase velocities for the longitudinal and transverse versus the amount of damage is done for different relative densities evaluated versus the percentage of damaged beams for the square and triangular network. The effective mechanical properties of the overall network are evaluated as a function of the increasing damage based on a numerical procedure. Computations show that the square lattice has higher phase velocities in comparison with the triangular lattice. This work sets the basis of a methodology for evaluating the state of damage in network materials based on the changes in the wave propagation velocities.